1991 Press-School Awards (Journal of Parents and Teachers, 2026)
This article highlights some of the experiences of various schools in Spain that took part in the fifth edition of the Prensa-Escuela awards, established by the Ministry of Education and Science and the Association of Spanish Newspaper Publishers (AEDE). The aim of these awards is to encourage pupils to use the press, develop reading habits and cultivate a critical mindset. The work in each school has been carried out by teachers and pupils at different educational levels and in different subject areas, using newspapers and magazines for this purpose.
Keywords: press; school; Press-School Awards; critical thinking